A Preliminary Investigation of the Potential Costs and Benefits of Rehabilitation of the Nakivubo Wetland, Kampala - Turpie, Jane; Day, Liz; Gelo Kutela, Dambala; Letley, Gwyneth; Roed, Chris; Forsythe, Kat (World Bank, Washington, DC, 2017)
Rapid urbanisation threatens existing natural areas withincities and the ecosystem services that they provide. This case study forms part of a broader study that investigates the benefits of investing in Green Urban Developmentin African cities. The Kampala case study focuses on the Nakivubo wetland, one of several large wetland systems that occur within and around the city. This wetland has become severely degraded by polluted water from thecity that passes through the wetland before entering Inner Murchison Bay. However, as the city has continued to grow, pollution flows into the wetland have increased significantly, the size and assimilative capacity of the wetland has decreased, and the costs of water treatment have increased. These concerns, as well as the increasing shortage of public open space areas in the city that are available for recreation, haveled to the city’s consideration of the rehabilitation of the Nakivubo wetland, both to restore its functioning and to create the opportunity for a recreational area with associated possibilities for economic development. This study provides a preliminary evaluation of the state of the Nakivubo wetland, the potential costs and benefitsof its rehabilitation and the implications for the city’sexpansion plans. The primary objectives were defined as(1) effecting a measurable improvement of waterquality passing out of the Nakivubo wetland into InnerMurchison Bay, (2) ensuring sustainable management ofthe Nakivubo wetland, (3) reducing water quality impactson human health and (4) opening up opportunitiesfor safe recreational use of the lower wetland. One of the main challenges in achieving the above would be institutional. Greater Kampala extends well beyond the boundaries of the Kampala Capital City Authority (KCCA), which originally encompassed the entire city, and unless the KCCA area is adjusted accordingly (as has been done in other countries), the problems that will arise in a growing city will be in areas under multiple other jurisdictions.